Using operational scenarios in a virtual reality enhanced design process - Aylward, Katie A; Dahlman, Joakim; Nordby, Kjetil; Lundh, Monica (Education Sciences, 2021)
Maritime user interfaces for ships’ bridges are highly dependent on the context in which they are used, and rich maritime context is difficult to recreate in the early stages of user-centered design processes. Operations in Arctic waters where crews are faced with extreme environmental conditions, technology limitations and a lack of accurate navigational information further increase this challenge. There is a lack of research supporting the user-centered design of workplaces for hazardous Arctic operations. To meet this challenge, this paper reports on the process of developing virtual reality-reconstructed operational scenarios to connect stakeholders, end-users, designers, and human factors specialists in a joint process. This paper explores how virtual reality-reconstructed operational scenarios can be used as a tool both for concept development and user testing. Three operational scenarios were developed, implemented in a full mission bridge simulator, recreated in virtual reality (VR), and finally tested on navigators (end-users). Qualitative data were captured throughout the design process and user-testing, resulting in a thematic analysis that identified common themes reflecting the experiences gained throughout this process. In conclusion, we argue that operational scenarios, rendered in immersive media such as VR, may be an important and reusable asset when supporting maritime design processes and in maritime training and education.